2012
DOI: 10.5999/aps.2012.39.5.497
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Reconstructed Breast Flap after Chemotherapy and Radiotherapy in Immediate Breast Reconstruction

Abstract: BackgroundPostmastectomy adjuvant therapy is used to prevent locoregional recurrence and improve overall breast cancer specific survival rates. However, it can adversely affect the cosmetic results of reconstruction. Therefore, the authors examined flap stability and patients' satisfaction with immediate breast reconstruction after adjuvant therapy.MethodsWe retrospectively reviewed the medical records of 204 patients from January 2006 to November 2011. For complication rates, the authors categorized the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…23e25 An increasing number of patients with BRCA combine radiotherapy and breast reconstruction. 13,26 Although the adverse effects of radiotherapy after implant-based reconstruction are well documented, 27 there is division of opinion over the outcome of autologous reconstruction when combined with PMRT. 13 Some studies have reported higher rate of complications, volume loss and flap shrinkage, and poor aesthetic outcomes, whereas more recent studies have found acceptable results in particular with modifications of radiotherapy regimes.…”
Section: Introductionmentioning
confidence: 99%
“…23e25 An increasing number of patients with BRCA combine radiotherapy and breast reconstruction. 13,26 Although the adverse effects of radiotherapy after implant-based reconstruction are well documented, 27 there is division of opinion over the outcome of autologous reconstruction when combined with PMRT. 13 Some studies have reported higher rate of complications, volume loss and flap shrinkage, and poor aesthetic outcomes, whereas more recent studies have found acceptable results in particular with modifications of radiotherapy regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is no definitive conclusion if preoperative chemotherapy and radiation are risk factors for flap viability. 12,14,[32][33][34][35][36][37][38][39][40] Surgeons may have rated radiation and chemotherapy as less of a risk factor than hematologists because they routinely use flaps in oncologic patients receiving adjuvant therapy.…”
Section: Risk Factorsmentioning
confidence: 99%